Listeria monocytogenes survival during production and storage of water buffalo Mozzarella cheese. (23rd August 2017) - Murru, Nicoletta; Peruzy, Maria Francesca; De Carlo, Esterina; Mercogliano, Raffaelina; Aponte, Maria; Morena, Carmelo; Serluca, Giovanna; Fraulo, Pasquale
Abstract : The ability of Listeria monocytogenes to survive during the manufacture of water buffalo Mozzarella and to grow during its shelf life was evaluated. A wild‐type and a reference strain were used to contaminate raw milk. The viable count of the reference strain ATCC 9525 dropped after the stretching process, and in the cheese, it fell to below 100 cfu/g. When the wild‐type strain was used, however, stretching did not appear to have any effect on the pathogen. The artificially contaminated cheeses were stored, for eleven days, at 4, 20 and 30 °C. Pathogen populations increased at 20 (≈2.60 log cfu/g) and 30 °C (≈1.95 log cfu/g).